Pengaruh Cashback, Flash Sale, dan Gratis Ongkos Kirim Terhadap Minat Beli Pada Event Twin Date Shopee di Kalangan Mahasiswa FEBM UMRAH - Ummu Nur Syahidah, Nadzifa; Paramita, Bunga; Ilham, Edinur (Bahtera Inovasi, 2025)
The study aims to examine the influence of cashback, flash sale, and free shipping on the purchase intention of FEBM UMRAH students during Shopee’s twin date events. A quantitative approach was used, with the population beng active FEBM UMRAH students who made purchases during the twin date events. A total of 94 respondents were selected using insidental sampling. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, an the coefficient of determination with SPSS version 26. The resulting regression model is Y = 2,542 + 0,464X1 + 0,686X2 + 0,154X3 + e with and Adjusted R2 of 0,687 or 68,7%. The t-test results indicate that cashback (X1) and flash sale (X2) have a positive and significant effect on purchase intetion, while free shipping (X3) has a positive but not significant effect. The F-test shows that all three variables simultanaeously have a significant effect, with F-valu of 69.095 > F-table 2,71 and significance of 0,000<0,05. Thus, it can be conducted that promotion strategies involving economic incentives and urgency effectively increase students purchase intentions during Shopee’s events